The absence of the fathers' role and its impact on school bullying among adolescents - Haifa, Nagham Anis (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to reveal the level of school bullying among the members of the research sample, and to reveal the differences in the level of school bullying among the members of the research sample according to the following variables (gender, school class, type of absence).The research sample consisted of (90) teenage boys and girls from the class the eighth and eleventh from the Damascus countryside governorate, and the researcher used a scale (Mohammed, 2020).The results of the research showed the presence of a medium level of school bullying among the members of the research sample, and the presence of statistically significant differences among the research sample according to the study variable (gender) on the scale of school bullying. And the absence of statistically significant differences among the members of the research sample according to the study variables (school class- type of absence) on the scale of school bullying.
Keywords: The absence of the role of parents; school bullying; adolescents